Direct payments for areas under hemp plantations - Łata, Monika (Przegląd Prawa Rolnego, 2024)
The aim of the considerations is to determine the legal nature of the payments for areas cultivated with hemp in the light of EU and national law and to formulate an answer to the question whether the legal construction of this payment is in line with the objectives of the Common Agricultural Policy drawn for the period 2023-2027. It has been established that these payments have a conditional character. Indeed, the legislator burdens the agricultural producer with the risk of not receiving any area payments on the area of cultivation of hemp since support is determined by the percentage content of Δ9-tetrahydrocannabinol in the cultivated variety of hemp, which is variable and de facto independent of the farmer. This contradicts the objectives of the CAP, such as promoting fair farm incomes and the resilience of the agricultural sector across the Union, or increasing market orientation and ensuring the competitiveness of farms. The author notes the inconsistency of the Polish regulation of fibre hemp with EU law. It is therefore proposed that the definition of "eligible hectare" in relation to hemp in EU law be clarified, and the EU method for verifying the Δ9-tetrahydrocannabinol content in the Polish legal order in a comprehensive manner be implemented, alongside with the adaptations of the provisions of the Act on Counteracting Drug Addiction to the new conditions.